Electrodeposition and Performance of Ti/SnO2-Sb/PbO2 Electrodes from Methanesulfonate Baths. Issue 10 (20th June 2019) - He, Xiaohong; Xu, Pengfei; Mao, Junwei; Tang, Yongming
Abstract : Electrodeposition of PbO2 films from methanesulfonate (MSA) baths onto Ti/SnO2 -Sb substrates are studied in this paper. With increasing the concentration of MSA, the growth of α-phase PbO2 is preferred. Adsorption of MS ions on surface enhances the preferential orientations of α (0 2 0) and β (3 0 1) planes, and favors the formation of dense and uniform PbO2 film with deposition time. The presence of Bi 3+ ions in the baths facilitates the growth of β-phase PbO2 instead of α phase, and at the same time, inhibits the formation of nonstoichiometric PbO2 by replacing the Pb (II) in the lattice defects. The improvement in both morphology and service lifetime is achieved by the low-level Bi inclusion. In contrast, the high-level Bi inclusion results in a shorten service lifetime and higher oxygen evolution current density.